EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI ANAK DI PANTI ASUHAN CABANG ‘AISYIYAH MATUR - Rina Wati Putri; Syawaluddin; Yusraini (CV. ADIBA AISHA AMIRA, 2024)
Group tutoring is the provision of services in a group atmosphere by utilizing group dynamics. This research started from the fact that there were some children from the 'Aisyiyah Matur branch of the orphanage who were shy when communicating with their environment, especially with people they had just met, then there were also some children who often stayed alone in their rooms rather than joining their friends. There are also children who are insecure because of their condition and status as well as children who often avoid being asked questions so that children like this can be said to lack self-confidence. Researchers tried to apply group guidance to increase the self-confidence of children in the orphanage. This research itself aims to reduce feelings of inferiority and increase self-confidence in orphanage children. The method used in this research is quantitative with the type of pre-experimental research, one group pre-test, post-test. The subjects of this research were children at the 'Aisyiyah Matur branch of the orphanage who lacked self-confidence. The data analysis technique uses the Wilxocom rank test. The research instrument used in this research is a measurement scale in the form of a questionnaire. The results of this research can be seen from the implementation of the pre-test and post-test with an increase in each child. Wilxocom signed rank test analysis shows a value of 0.012 < 0.05, so it can be concluded that there is an increase in self-confidence through group guidance at the 'Aisyiyah Matur branch of the orphanage.